ASSESSMENT OF THE SATISFACTION LEVEL OF CONSUMERS TOWARDS ENERGY EFFICIENT SOLAR PRODUCTS IN COIMBATORE CITY - C. ANUPAMA * and M. R. THILAKAM (The Journal of Research ANGRAU, 2022)
The data of 400 households using one solar device from Coimbatore city was gathered betweenJuly 2019 and January 2020.The magnitude of the satisfaction level of consumers based on gender,age and qualification was calculated, t-test of equality of means was applied to understand the meanscore of satisfaction level among males and females. Similarly, ANOVA was performed to know themean score of satisfaction level among different age groups and qualifications. The outcome of thestudy substantiated that consumer satisfaction level towards energy efficient solar products wassignificantly determined by socio-demographic factors of consumers. The results of study disclosedthat almost thirty-five percent of participants were satisfied with the aspect easy installation of solardevices whereas nearly 28.5 percent of the participants were highly satisfied. Whereas, 47.5 ofpercent participants were satisfied by easy operation and maintenance of solar devices. A significantnumber of participants (44.8 percent) were satisfied with the durability of the solar device. Twentyfourpercent of the solar device users communicated that they are highly satisfied with the availabilityof after sales-services.